Peer Feedback to Improve Speaking Skills through Vocaroo, a Voice Recording Application - Franco Bayas, Miguel Andrés (2022)
The innovation consisted of using peer feedback through Vocaroo, an online Voice Recording Application to improve speaking skills. The distribution of time for this innovation was for 25 hours compound from 5 weeks, divided in 3 synchronous hours, 2 asynchronous hours. It was necessary to find a suitable schedule during the cycle November 2021 – April 2022, not to interrupt the synchronous classes from the institution according to the timetable. The target group needed to improve their speaking skills and the application of this innovation totally fit in it.